FENOMENA FANWAR DALAM FANATISME PENGGEMAR KPOP PADA MEDIA SOSIAL TWITTER - Zahrah Zahirah Salsabila (Master of Communication Science Program, Universitas Diponegoro, 2024)
This study determine Phenomenon of Fanwar in Kpop Fanaticism on Twitter Social, used Computer Mediated Communication (CMC) and data collected through primary and secondary. The results showed fanwar behavior on Twitter was caused by addiction of KPop fans into fanaticism. Fanaticism happened because of the ease features on Twitter very effective for fan activities, the speed information updates and the obsession with idols because see them on twitter in a daily life. KPop fanwar are included by randomly attack groups that aren’t idolized, lead inappropriate opinions in impolite language, use empty accounts only to attack idols and fans, a solo stan or shipper stan compared one group to another, and bring down the achievements of other idols. This study found negative impacts from fanwar are wasting time, sense of regret after participating in fanwar, mood and feelings become bad, fandom and idols will be judged not good, and friendship disputes that occur in the real world. While the positive impact is daring to express opinions, relieve emotions and can be used as a topic of conversation with non-KPop fans because it is considered a joke or entertainment topic only.